Sistem Informasi Monitoring Siswa Berbasis Web Dan SMS Gateway Pada SMK Negeri 37 Jakarta - Maharani Enggar Putri; Dewi Ayu Nur Wulandari (JURNAL TEKNIK KOMPUTER AMIK BSI, 2016)
SMK Negeri 37 Jakarta is one of the vocational high school located in South Jakarta. The purpose of school authorities is improving student discipline related to the improvement of student discipline in schools is the presence in the classroom or in the call attendance . The parents are still very concerned about the condition of children in school , whether they are really-really go to school or not , and parents can not determine the development of how the values obtained her directly because of busy work even for children less open to question the value obtained in school . Therefore , system monitoring information required by the school students of SMK Negeri 37 Jakarta to communicate information to parents directly related to the state of their students in school through sms information with computerized data processing using the web interface . Keywords : Student Information System Monitoring, Web, SMS gateway